Reimagining Democracy - Stephanie Mae Pedron (Politikon)
In this brief Conversations essay, I trace how immigrant suffrage in the United States deteriorated in the 19th century and argue that the US should move toward creating a pathway for noncitizen voting for two reasons—a more representative democracy and for a smoother assimilation process into American culture. Noncitizens contribute economically and socially to their communities, and they often have the same investment in their community’s welfare as citizens. Expanding voting rights to noncitizens, even if only at the local-level, would give them a voice in decisions that affect their everyday lives.